Maize (Zea mays) genotypes for intercroping with cassava (Manihot esculenta) in southern Nigeria; 1: yield responses - Ezumah, H.C. (1990)
Five maize genotypes differing in plant habit and growth period were evaluated at 5 population densities (10, 20, 40, 80 and 160 × 103 plants/ha) under an intercropping system with cassava at 1 × 1 or 1 × 0.67 m spacings in a tropical Alfisol in southern Nigeria. The 2-year study revealed significant cassava spacing (CS) × maize spacing (MS) and CS × MS × maize genotype interactions for cassava root yield. Maize populations of up to 40 × 103 plants/ha gave no significant reduction in cassava root yield compared with the base (10 × 103) population. Maize density had no effect on cassava root yield in the favourable year (1985) but increased density caused yield reductions in the drought year (1986). Maize variety effects were also more pronounced during 1985. It was concluded that maize populations as high as 40 to 80 × 103 can be used for intercropping with cassava without significant effects on cassava root yield in years with adequate rainfall. The optimum maize population varies, however, with maize height, time to maturity and amount of rainfall; short, early maturing genotypes can be used at the higher densities.